Analysis on vibration characteristics of tubing under pressure operation. (November 2020) - Hong, Yukui; Dong, Liangliang; Tang, Geng; Xie, Youli; Chen, Malin; Liu, Xiaodong; Liu, Rui; Yang, Lei
Abstract: Pressure operation is a kind of advanced down hole technology which can be used to lift and lower the string under the condition of maintaining a certain pressure in the wellbore, not killing the well or releasing the pressure. However, due to the pressure fluctuation at the front end of the string, the string vibration is caused, which is extremely unfavorable to the operation with pressure. According to industry data, in a series of oilfield safety incidents from 2008 to 2015, nearly 65 %o of the total was due to vibration in the downhole string. Therefore, it is necessary to further study the factors affecting the vibration of the pipe string, so as to reduce the influence of the pipe string vibration, which is also an important means to avoid accidents. In this paper, the dynamic grid method is applied to the numerical simulation analysis of the pipeline, and the pressure fluctuation at the front end of the pipe string is obtained. At the same time, the influence of different shapes at the front end of the pipe string on the vibration of the pipe string is studied, which provides a certain theoretical background for relevant scholars.